Reading History in Historical Literature: An Analysis of the Historical Novel Kalbu Qalha: (Membaca Sejarah dalam Karya Sastera: Analisis Novel Sejarah Kalbu Qalha) (Malay Literature, 2019)
History has long been a source of inspiration for creative works in the effort of writers to produce quality literature. This is because there exist truths in history that can be conveyed to readers or audiences for the purpose of joint contemplation. In this article, historical events are examined through Amelia Hashim's latest novel, Kalbu Qalha [The Heart of Qalha], which is set against the history of Kedah, from its early beginnings through Siamese occupation and finally British interference. The analysis of the novel in this article employs the theoretical framework of Lukács to show that history can be read through literary works. This novel successfully exposes history and little-known historical figures to its readership, proving that historical literature is not mere fiction.Keywords: Kalbu Qalha, historical novel, history, Amelia Hashim, Kedah